Palladium complex immobilized on SBA-15 as an efficient catalyst for the heck reaction of aryl iodides with styrene - Son Nam, Phan Thanh; Le Nhon, Nguyen Thi (Vietnam Journal of Chemistry, 2014)
Highly ordered mesoporous silica SBA-15 was synthesized and functionalized via silane chemistry with N-[3-(trimethoxysilyl)propyl]ethylenediamine to create surface amino groups. The amino-functionalized SBA-15 was allowed to react with 2-acetyl pyridine to form an immobilized bidentate iminopyridine ligand, which was complexed with palladium acetate, affording the immobilized palladium complex catalyst with a palladium loading of 0.4 mmol/g (AAS). The catalyst was characterized by X-ray powder diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), thermogravimetric analysis (TGA), Fourier transform infrared (FT-IR), nitrogen physisorption measurements, and elemental analysis (EA). The immobilized palladium complex was used as an efficient heterogeneous catalyst for the Heck cross-coupling reaction of iodobenzene and styrene to form stilbene as the principal product. The reaction was carried out in dimethylformamide (DMF) at 140oC, in the presence of triethylamine as a base, and at the catalyst concentration of 0.1 mol% palladium. Excellent conversions (more than 99%) were achieved after 5 hours. It was also observed that the modified SBA-15 catalyst could be facilely separated from the reaction mixture by centrifugation, and could be reused in subsequent reactions without significant degradation in activity.